Work engagement pada karyawan: Bagaimana peranan perceived organizational support? - Maulana, Setiawan; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
Abstract This research was conducted to determine the relationship between perceived organizational support and work engagement. The subjects of this study were all employees as sales assistants at PT. Mitra Adi Perkasa with 115 employees. The sampling technique used random sampling. Data collection uses the perceived organizational support scale and work engagement scale. The results of the Spearman correlation coefficient test (rxy) were 0.419 at a significance level of p=0.000 (p<0.01). Based on the results obtained, it can be concluded that there is a very significant relationship between perceived organizational support with work engagement. The results of the study provide knowledge to companies and employees to increase perceived organizational support for employees so that they can increase work engagement and achieve company targets. Keywords: Work Engagement, Perceived Organizational Support.